Acute and longitudinal changes in red blood cell parameters during intense training in international amateur boxers - Child, R. B.; Smith, M. S.; Draper, S. B.; Irwin, I.; Wilkinson, D. M. (2001)
Iron deficiency and increased haemolysis have been identified as contributory factors to anaemia in gymnasts, wrestlers and endurance runners. Similar data are not available for elite boxers during training. Therefore this study assessed haematological parameters at three boxing camps over a 3 month period. Nine international amateur boxers consented to blood sampling at each five day training camp, involving boxing specific exercises, running and weight training. Venous blood was drawn at rest, prior to and at the end of each training camp. Samples were analysed for hematocrit and the concentration of haemoglobin in whole blood and the plasma concentrations of bilirubin, ferritin and c-reactive protein. Data are presented as means ± SEM and were analysed using repeated measures analysis of variance. Prior to the first training camp resting haematocrit, haemoglobin, bilirubin, ferritin and c-reactive protein were 46.5± 1.3%, 9.57± 0.2 mmol.l-1, 16.7± 2.3 mmol.l-1, 68± 20 ng.ml-1 (range 20 to 203 ng.ml-1) and less than 6± 0 mg.l-1 respectively. Acute training effects included a significant decrease in plasma haematocrit (P<0.01) and an increase in plasma bilirubin (P<0.05); however the plasma bilirubin concentration decreased over time (P<0.001). Acute but non-significant elevations in ferritin were observed in response to training (P>0.05), however over time there was trend towards reduced plasma ferritin (P=0.110) and at the end of the study the mean ferritin concentration was 54± 11 ng.ml-1 (range 17 to 101 ng.ml-1). No changes in c-reactive protein were observed throughout the investigation. These data suggest that intense boxing training results in a considerable increase in red blood cell destruction, which does not appear to be matched by a parallel increase in red blood formation. In two boxers with ferritin levels below 20 ng.ml-1, red cell formation could have been compromised by low iron stores.